The shame of it : global perspectives on anti-poverty policies / edited by Erika K. Gubrium, Sony Pellissery and Ivar Lødemel. - Gubrium, Erika K.; Lødemel, Ivar; Pellissery, Sony, 1972- (The Policy Press, 2014)
This important volume provides the foundation for a shift in policy learning on a global scale and demonstrates the need to take account of the psychological consequences of poverty for policy to be effective.